Films for Wound Healing Fabricated Using a Solvent Casting Technique - Fabiola V. Borbolla-Jiménez; Sheila I. Peña-Corona; Sonia J. Farah; María Teresa Jiménez-Valdés; Emiliano Pineda-Pérez; Alejandra Romero-Montero; María Luisa Del Prado-Audelo; Sergio Alberto Bernal-Chávez; Jonathan J. Magaña; Gerardo Leyva-Gómez (MDPI AG, 2023)
Wound healing is a complex process that involves restoring the structure of damaged tissues through four phases: hemostasis, inflammation, proliferation, and remodeling. Wound dressings are the most common treatment used to cover wounds, reduce infection risk and the loss of physiological fluids, and enhance wound healing. Despite there being several types of wound dressings based on different materials and fabricated through various techniques, polymeric films have been widely employed due to their biocompatibility and low immunogenicity. Furthermore, they are non-invasive, easy to apply, allow gas exchange, and can be transparent. Among different methods for designing polymeric films, solvent casting represents a reliable, preferable, and highly used technique due to its easygoing and relatively low-cost procedure compared to sophisticated methods such as spin coating, microfluidic spinning, or 3D printing. Therefore, this review focuses on the polymeric dressings obtained using this technique, emphasizing the critical manufacturing factors related to pharmaceuticals, specifically discussing the formulation variables necessary to create wound dressings that demonstrate effective performance.